RELOCATING INCLUSIONARY HOUSING OBLIGATIONS TO THE NEW CAPITAL NUSANTARA: LEGAL AND POLICY IMPLICATIONS - Hermawan, Muhammad Ilham; Herliana, Nasywa Ananda (UI Scholars Hub, 2024)
The philosophical meaning of balanced housing lies in achieving a harmonious and equitable life among various social strata. To realize this philosophical essence, regulatory engineering is required, aimed at fulfilling the goals of balanced housing. The obligation for balanced housing is theoretically known in the literature of several countries as an inclusionary housing policy. Triggered by the need for residential development in the new capital city (IKN), the Government has